PENGARUH PERENDAMAN TERHADAP NILAI CBR PADA TANAH LEMPUNG YANG DISTABILISASI DENGAN ABU CANGKANG SAWIT DAN KAPUR - Kurniawan, Deddy (Ensiklopedia of Journal, 2018)
Soil is one of the construction materials that are directly available in field, various means are used to improve the strength of soil clays, such as by the addition of chemicals. In order to find out the existing problems on the ground then conducted research using Palm Shell Grey and lime as a material stabilization . Clay soil samples taken from the road bypass KM 56 pariaman as deep as 1 m. The face of the ground at a distance of 30 m from the outer width of the road, while the stabilization material used is Palm shell ash percentage ash mixture and lime Shell Oil amounting to 9% and 5% of lime with the submersion of 0, 1, 4, 7 and 14 days. The method of this research is experimental research that is done by holding the object against the manipulation of research as well as the presence of the control. In the experiment, researchers manipulation a treatment or experimental conditions, and then observing the influence caused by the treatment or manipulation. The research results show the test results of the original ground soaking CBR 0 and 14 days test result shows that the original land CBR 0 day 60.85% and 2.20% 14 days is lower than the CBR test results of soil with a mixture of palm oil shell ash 9% and 5% lime by submersion 0 days 74.2% and 14 days 65% increment happened, the longer the immersion indicates the more increasing the CBR test results, seeing from the results of the immersion test 0, 1, 4, 7, and 14 days, at the 14-day immersion the best results were obtained.